Pendampingan Masyarakat dalam Penguatan Ekonomi Hijau Berbasis Nilai Qurani dan Fikih Lingkungan - Zulaika Zulaika; Duwi Aditya; Muhammad Risyad Maulidi; Muhammad Alfalenky; Muhammad Azhari; Nadianti Nadianti; Muhammad Syahdani (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2026)
This community service program aims to strengthen community capacity in developing green economy practices based on Qur’anic values and environmental fiqh as an ethical foundation for natural resource management. The program was initiated in response to the low level of ecological awareness and the suboptimal utilization of sustainable local economic potential, which have contributed to environmental degradation and limited economic self-reliance within the community. Implemented through a participatory mentoring approach, the program involved thematic training, focus group discussions, and field practices integrated with Islamic values. Data were collected through participatory observation, in-depth interviews, and documentation, and analyzed qualitatively to identify changes in community understanding, attitudes, and practices. The findings reveal positive changes in community awareness regarding the relationship between economic activities and environmental sustainability, as reflected in increased participation in environmental management activities, the emergence of community-based waste management initiatives, more environmentally friendly land-use practices, and the development of sustainability-oriented productive enterprises. Furthermore, the integration of Qur’anic values and environmental fiqh strengthened community awareness and motivation to preserve the environment as part of their social and religious responsibilities. These findings indicate that a religious values-based mentoring approach can serve as an effective strategy for promoting green economy development and sustainable community empowerment at the local level.